The `small town` effect on youth athletic development: insights from New Zealand `touch` - Pennell, K.; Cassidy, T.; Gilbert, W. (Qualitative Research in Sport, Exercise and Health, 2017)
There is a growing worldwide interest in understanding optimal and healthy pathways for talent development in sport. The purpose of the study was to explore how familial, environmental and social factors facilitated the athletic development of elite Touch representatives who grew up in the small town of Petersville (pseudonym), New Zealand. An interest in understanding these factors influenced the decision to use an ecological model of development as an analytical lens and to apply (auto)ethnographic methodologies. The participants, which included the first author, grew up in Petersville and had represented New Zealand in the sport of Touch, in various capacities, i.e. of player, referee and manager. While the primary focus is on athletic development of the players who grew up in Petersville, they grew up in a community in which other members were active in the elite NZ Touch community. Consistent with an ecological view of development, the discussion illustrates how influential the referee (who was also the coach of the school Touch team) and the manager were to player development. The findings contribute to the literature by demonstrating a nuanced interpretation of the `birthplace effect`, particularly in countries with small populations and limited geographical areas.